Modern Faraday Rotation Studies to Probe the Solar Wind - Kooi, Jason E.; Wexler, David B.; Jensen, Elizabeth A.; Kenny, Kenny N.; Nieves-Chinchilla, Teresa; Wilson, Lynn B.; Wood, Brian E.; Jian, Lan K.; Fung, Shing F.; Pevtsov, Alexei; Gopalswamy, Nat; Manchester, Ward B. (Frontiers in Astronomy and Space Sciences, 2022)
For decades, observations of Faraday rotation have provided unique insights into the plasma density and magnetic field structure of the solar wind. Faraday rotation (FR) is the rotation of the plane of polarization when linearly polarized radiation propagates through a magnetized plasma, such as the solar corona, coronal mass ejection (CME), or stream interaction region. FR measurements are very versatile: they provide a deeper understanding of the large-scale coronal magnetic field over a range of heliocentric distances (especially ~1.5 to 20 solar radii) not typically accessible to in situ spacecraft observations; detection of small-timescale variations in FR can provide information on magnetic field fluctuations and magnetohydrodynamic wave activity; and measurement of differential FR can be used to detect electric currents. FR depends on the integrated product of the plasma density and the magnetic field component along the line of sight to the observer; historically, models have been used to distinguish between their contributions to FR. In the last two decades, though, new methods have been developed to complement FR observations with independent measurements of the plasma density based on the choice of background radio source: calculation of the dispersion measure (pulsars), measurement of Thomson scattering brightness (radio galaxies), and application of radio ranging and apparent-Doppler tracking (spacecraft). New methods and new technology now make it possible for FR observations of solar wind structures to return not only the magnitude of the magnetic field, but also the full vector orientation. In the case of a CME, discerning the internal magnetic flux rope structure is critical for space weather applications.